(untitled) (Historia, 2021)
This article examines historically black universities (HBUs), in particular the University of Fort Hare, as heritage sites. It argues that one aspect of universities is to act as symbols of the intellectual and cultural achievements of particular societies or classes. The ambiguous origins and past of South African HBUs has made it difficult for them to fulfil this role in relation to African society : Fort Hare with its longer and more complex history can attempt to do so with more conviction. The article outlines the history that makes it possible for Fort Hare to present itself as a symbol of African achievement, and describes the art gallery, archives and museum that are amongst the physical and intellectual manifestations of these achievements.